Nine-year clinical evaluation of composite resins in Class III restorations - Sá, Fátima Cristina; Fagundes, Ticiane Cestari; Baseggio, Wagner; Bresciani, Eduardo; Barata, Terezinha Jesus Esteves; Franco, Eduardo Batista (Brazilian Dental Science, 2015)
Objective: The aim of this study was to evaluate the nine-year clinical performance of Class III composite restorations using two microhybrid anterior composite resins [Magic™-Vigodent/(F) and Z100™-3M ESPE/(Z)]. Material and Methods: The study was a randomized controlled trial, following the split mouth design. Seventy restorations were placed, thirty-five for each resin composite into 35 patients. The restorations were placed by one operator according to the manufacturers’ specifications. Two independent evaluators conducted the clinical evaluation using modified USPHS criteria. After nine-years, 56 restorations (28F-28Z) were evaluated. Data were analyzed using Chi-square, Exact Fisher and McNemar tests (p